Region-Specific Changes of Insular Cortical Thickness in Heavy Smokers - Lin, Fuchun; Wu, Guangyao; Zhu, Ling; Lei, Hao (Frontiers in Human Neuroscience, 2019)
Insula plays an essential role in maintaining the addiction to cigarette smoking and smoking-related alterations on the insular volume and density have been reported in smokers. However, less is known about the effects of chronic cigarette smoking on the insular cortical thickness. In this study, we explored the region-specific changes of insular cortical thickness in heavy smokers and their relations with smoking-related variables. Thirty-seven heavy smokers (29 males; mean age 47.19±7.22 years) and 37 nonsmoking healthy controls (29 males; mean age 46.95±8.45 years) participated in the study. Subregional insular cortical thickness was evaluated and compared between the two groups. Correlation analysis was performed to investigate relationships between the insular cortical thickness and clinical characteristics in heavy smokers. There was no statistical difference on the cortical thickness in the left insula (p=0.536) between the two groups while heavy smokers had a slightly thinner cortical thickness in the right insula (p=0.048). In addition, heavy smokers showed a greater cortical thinning in the anterior (p=0.0084) and superior (p=0.0054) segment of the circular sulcus of the right insula as well as the inferior (p=0.012) segment of the circular sulcus of the left insula. Moreover, the cortical thickness of the superior segment of the circular sulcus of the left insula was correlated negatively with nicotine severity (r=-0.423; p=0.009) and the longer cigarette exposure was associated with the cortical thinning in the long insular gyrus and central sulcus of the right insula (r=-0.475; p=0.003). Our findings indicate that chronic cigarette use is associated with region-specific insular thinning, which has the potential to improve our understanding of the specific roles of insular subregions in nicotine addiction.